The mediating effect of safety management system on the relationship between safety culture and safety performance in Lagos food and beverage manufacturing industries - Otitolaiye, Victor Olabode (2016)
Occupational safety in organizations is essential for continuous existence and sustainable growth of a nation. The continuous high frequency of occupational accidents in Nigerian Food & Beverage (F&B) industries calls for a new approach to stem the tide. In order to cope with the challenges and achieve superior performance, organizations need to develop a positive safety culture (SC). Furthermore, the organizations need to implement an appropriate safety management system (SMS). This issue has motivated the embarkment of this study to investigate the mediating effect of safety management system on the relationship between safety culture and safety performance of F&B industries in Lagos, Nigeria. Data was collected from 126 head of safety managers through self-reported questionnaires and data analysis was done using the SmartPLS 2.0. Findings reveal that safety culture and safety management system are significantly and positively related to safety performance. Further analysis indicates that safety management system mediates the relationship between safety culture and safety performance. Thus it is concluded that although safety culture is positively and significantly related to safety performance, however the effect of safety culture on safety performance will be greater if the organizations develop and continuously implement a strong safety management system.